2021
DOI: 10.3390/pharmaceutics13040559
|View full text |Cite
|
Sign up to set email alerts
|

Dual Inhibition of P-gp and BCRP Improves Oral Topotecan Bioavailability in Rodents

Abstract: P-glycoprotein (P-gp) inhibition has been studied to overcome multidrug resistance in cancer chemotherapy but failed in clinical trials due to low/toxic effects. Recently, a dual modulation of transporters and natural derivatives have been examined to surmount this limitation. We examined breast cancer resistance protein (BCRP) inhibition in vitro and in vivo by P-gp inhibitors derived from natural compounds in previous studies. P-gp inhibitors increased the accumulation of the anticancer drug, topotecan (TPT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Many investigations are routinely performed to enhance the absorption of oral formulations. In particular, these studies aim to optimize drug solubility/permeability properties and inhibit P-gp and BCRP transporters [ 136 ] using excipients that can eventually favor drug absorption. For example, D-α-tocopherol polyethylene glycol 1000 succinate and PEG-400 were shown to increase the solubility and absorption of etoposide [ 137 ], and the research on generating novel, safe solvents is very intense [ 138 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many investigations are routinely performed to enhance the absorption of oral formulations. In particular, these studies aim to optimize drug solubility/permeability properties and inhibit P-gp and BCRP transporters [ 136 ] using excipients that can eventually favor drug absorption. For example, D-α-tocopherol polyethylene glycol 1000 succinate and PEG-400 were shown to increase the solubility and absorption of etoposide [ 137 ], and the research on generating novel, safe solvents is very intense [ 138 ].…”
Section: Discussionmentioning
confidence: 99%
“…Arimori et al [ 17 ] reported that the open/closed state of the ring changed the pharmacokinetics of CPT-11 and its affinity for P-glycoprotein, which is responsible for the extracellular transport of CPT-11. Topotecan is also a substrate for P-glycoprotein and breast cancer-resistance proteins [ 18 , 19 , 20 ]. Among the functional components of the blood–brain barrier and the blood–CSF barrier [ 21 ], proteins of the ATP-binding cassette transporter family appear to play a significant role in transporting topotecan and are likely to affect its distribution in the brain parenchyma and CSF compartments [ 18 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The USFDA drafted drug interaction guidelines for MDR1 (P‐gp) and BCRP (ABCG2) (Ou et al, 2021; Lee et al, 2021). In the epithelial cells, if the basal to apical (B–A) to apical to basal (A–B) efflux ratio of the new molecular entity (NME) is ≥2, then it is taken into account as a potential substrate of the P‐gp.…”
Section: Usfda Guidelines Related To P‐gpmentioning
confidence: 99%